Changes in Prefrontal Gamma-Aminobutyric Acid and Perfusion After the Computerized Relaxation Training in Women With Psychological Distress: A Preliminary Report - Namgung, Eun; Kim, Jungyoon; Jeong, Hyeonseok; Ma, Jiyoung; Hong, Gahae; Kang, Ilhyang; Kim, Jinsol; Joo, Yoonji; Kim, Rye Young; Lyoo, In Kyoon (Frontiers in Psychology, 2021)
Computerized relaxation training has been suggested as an effective and easily accessible intervention for individuals with psychological distress. To better elucidate the neural mechanism that underpins effects of relaxation training, we investigated whether a 10-session computerized relaxation training program changed prefrontal gamma-aminobutyric acid (GABA) levels and cerebral blood flow (CBF) in women with psychological distress. We specifically focused on women since they were reported to be more vulnerable to develop stress-related disorders than men. Nineteen women with psychological distress, but without a diagnosis of psychiatric disorders received the 10-day computerized relaxation training program that consisted of 30-minute cognitive-relaxation training and 10-minute breathing-relaxation training per day. At baseline and post-intervention, perceived stress levels, anxiety, fatigue, and sleep quality were assessed by self-report questionnaires. Brain magnetic resonance spectroscopy and arterial spin labeling scans were also performed before and after the intervention to evaluate GABA levels and relative CBF in the prefrontal region. Levels of perceived stress (t=4.02, P<0.001), anxiety (z=2.33, P=0.02), fatigue (t=3.35, P=0.004), and sleep quality (t=4.14, P<0.001) improved following 10 sessions of computerized relaxation training, resulting in significant relief in composite scores of stress-related symptoms (t=-5.25, P<0.001). The prefrontal GABA levels decreased (t=2.53, P=0.02), while relative CBF increased (t=-3.32, P=0.004) after the intervention. In addition, greater increase in relative prefrontal CBF was associated with better composite scores of stress-related symptoms following the intervention (t=2.22, P=0.04). The current findings suggest that computerized relaxation training may improve stress-related symptoms through modulating the prefrontal GABA levels and CBF in women with psychological distress.